ASSESMENT OF DETERMINANTS OF EFFCTIVE CHANGE IMPLEMENTATION IN THE COUNTY GOVERNMENTS: A CASE OF LAIKIPIA COUNTY - Gichuki, Evah Wangui; Abok, Dr. Alice (IJRDO - Journal of Business Management, 2015)
Public sectors worldwide are under pressure to increase efficiency while deliveringimproved and integrated services. The purpose of the study was to examine the factorsinfluencing effective change implementation in the county governments a case study ofLaikipia County with aim of making recommendations on effective changeimplementation. The study was aimed at establishing how top management support,communication, technology tools, and government policies affect effective changeimplementation. The study employed descriptive research design. A sample of 212 Laikipia County Government employees was selected through stratified randomsampling to participate in the study. Self-administered questionnaires were used tocollect data which was analyzed using SPSS versions 20 and presented in form ofrelevant graphs and tables. Most of the respondents agreed with the statement that topmanagement participates in ensuring successful delivery of services under the newchanges. Results showed that most of the respondents agreed that top managementdelegates and monitors duties on ensuring change management to ensure success.Most of the respondents agreed that government employment policy and regulationsaffect effective implementation of change in the County. Transition guidelines ondevolution influences change implementation in Laikipia County Government wassupported by most of the respondents while close to half agreed with presence ofadequate legal framework to support the implementation of change. The CountyGovernments have a great responsibility of ensuring that top management plays its rolein effective change implementation which is vital. To achieve this, proper and extensivemonitoring activities in change implementation should be provided to ensure itseffectiveness .